Integrating sport education model and the athletics challenges approach for transformative physical education in Indonesian Middle Schools - Rita Komalasari (Motion: Journal Research of Physical Education, 2023)
Physical education (PE) in Indonesian middle schools faces challenges, including outdated curricula and limited teacher development. This study investigates integrating the Sport Education model and Athletics Challenges approach to enhance PE. Sport Education aims to develop competent, literate, and enthusiastic sportspeople, while Athletics Challenges promotes inclusive group learning, self-assessment, and authentic athletic events. Literature analysis reveals positive outcomes, but lacks Indonesian context. This paper addresses gaps by proposing integration and analyzing it in the Indonesian middle school setting. Cultural nuances, practical experiences, and literature insights are explored. The study contributes novel insights by offering an integrated pedagogical model, cultural adaptation, teacher collaboration, student-centered learning, leadership development, and implications for policy and practice. The Ecological Systems Theory guides the analysis, providing a holistic framework to address diverse influences at micro, meso, exo, macro, and chrono levels. By merging pedagogical models, considering cultural contexts, and applying the theory, this study contributes to enriching PE and enhancing education in Indonesia.